2008
DOI: 10.1016/j.juro.2008.01.089
|View full text |Cite
|
Sign up to set email alerts
|

Prolapse and Incontinence Surgery in Older Women

Abstract: Purpose-Pelvic floor disorders including urinary incontinence, pelvic organ prolapse and fecal incontinence are common problems encountered by the older woman. With the increasing population of older American women, urologists and gynecologists can expect to provide evaluation and treatment of these conditions with increasing frequency. These conditions are amenable to both medical and surgical therapies.Materials and Methods-Contemporary published articles (year 2003 to present) that included older women unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…POP is a common condition with an estimated incidence of up to 40% of women and shows a growing prevalence in Western countries due to increased life expectancy [14]. 30% of women aged 50 -89 years require a consultation for pelvic floor dysfunction and the life-time risk of surgical repair is estimated at 11%, with almost one-third of the patients requiring repeat surgery.…”
Section: Resultsmentioning
confidence: 99%
“…POP is a common condition with an estimated incidence of up to 40% of women and shows a growing prevalence in Western countries due to increased life expectancy [14]. 30% of women aged 50 -89 years require a consultation for pelvic floor dysfunction and the life-time risk of surgical repair is estimated at 11%, with almost one-third of the patients requiring repeat surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Its prevalence is 37% in the general population, but increases to 64.8% in older women. 11 The association of POP and hydronephrosis differs across studies. Costantini et al 12 reported that the prevalence of hydronephrosis was 5% in patients with POP who were candidates for surgery, and bilateral in 3.1% versus unilateral in 1.9%.…”
Section: Discussionmentioning
confidence: 99%
“…All women aged 60 years and above undergoing pelvic floor surgery are classified as high-risk patients for thromboembolic complications owing to their age and other factors involved in undergoing major surgery. 2 Although pelvic floor surgeries seem to have low risk, postoperative DVT might occur more frequently than expected. In addition, patients with preoperative DVT are at high risk of postoperative DVT or pulmonary thromboembolism (PTE).…”
Section: Introductionmentioning
confidence: 97%
“…1 Likewise, the demand for POP care has been increasing in recent years. 2 Surgical procedures for POP include vaginal hysterectomy, colporrhaphy, the Le Fort operation, and tension-free vaginal mesh insertion, among others. These procedures are thought to be less invasive and safe, and therefore, the morbidity of these procedures is considered low.…”
Section: Introductionmentioning
confidence: 99%